PERAN INTELLECTUAL CAPITAL DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - I Putu Rana Mahendra Putra; A.A. Gede Krisna Murti; Putu Yudha Asteria Putri (Jurnal Riset Akuntansi Warmadewa, 2025)
This study aims determine and analyze the role of intellectual capital and good corporate governance on the financial performance of state-owned companies listed on the Indonesia Stock Exchange for the 2021-2023 period. State-Owned Enterprises (BUMN) are companies that have an important role for the national economy in realizing community welfare. This study uses a quantitative method using secondary data collected and published by other parties obtained from the Indonesia Stock Exchange website, namely www.idx.co.id and the Indonesia Capital Market Director. The data analysis technique used is panel data regression to test the relationship between independent variables (intellectual capital, good corporate governance), control variables (company size) with dependent variables (financial performance). The results of the study show that the three independent variables have a significant effect on financial performance. Based on the results of the hypothesis test, intellectual capital has a positive and significant effect on financial performance, good corporate governance has a negative and significant effect on financial performance, and company size has no effect on financial performance. Good corporate governance will help create conducive and accountable relationships between elements in the company, thereby increasing transparency and investor confidence.